Juridical Analysis of Inheritance Rights of Foreign-National Children Born from Mixed Marriages under the Indonesian Civil Code - Mandey, Aprilia Widya; Imon, Linda Lidia (Journal Social Civilecial, 2026)
Mixed marriages between Indonesian citizens and foreign nationals create complex legal consequences concerning citizenship, family status, inheritance rights, and ownership of property. This study aims to analyze the legal position of children born from mixed marriages and examine their inheritance rights under the Indonesian Civil Code when they possess or later choose foreign nationality. The research employed a normative juridical method using statute and conceptual approaches. Legal materials consisted of primary legal sources, including the Indonesian Civil Code, Law No. 1 of 1974 on Marriage, Law No. 12 of 2006 on Citizenship, Law No. 23 of 2002 on Child Protection, and Law No. 5 of 1960 on Basic Agrarian Principles, as well as secondary legal materials derived from doctrinal writings and scholarly literature. The findings demonstrate that Law No. 12 of 2006 provides limited dual citizenship protection for children born from mixed marriages until the age of eighteen years or marriage, followed by an obligation to choose one citizenship. Under the Indonesian Civil Code, a child born from a valid mixed marriage remains a lawful heir because inheritance rights are determined by a lawful civil relationship with the deceased parent rather than nationality alone. However, Indonesian agrarian law restricts foreign nationals from permanently holding ownership-title land. As a result, foreign-national heirs may inherit property rights but must transfer, release, or convert ownership-title land within the legally prescribed period. The study highlights the distinction between the right to inherit and the legal capacity to retain certain inherited assets while identifying continuing procedural and administrative challenges in cross-border inheritance disputes.